Electrically transmissive alkyne-anchored monolayers on gold. Issue 16 (10th April 2019) - Herrer, Lucía; González-Orive, Alejandro; Marqués-González, Santiago; Martín, Santiago; Nichols, Richard J.; Serrano, José Luis; Low, Paul J.; Cea, Pilar
Abstract : Well-ordered, self-assembled monolayer films of 1, 4-bis((4-ethynylphenyl)ethynyl)benzene on gold are shown to be nearly transparent to outer-sphere electron transfer processes. Abstract : Well-ordered, tightly-packed (surface coverage 0.97 × 10 −9 mol cm −2 ) monolayer films of 1, 4-bis((4-ethynylphenyl)ethynyl)benzene (1 ) on gold are prepared via a simple self-assembly process, taking advantage of the ready formation of alkynyl C–Au σ-bonds. Electrochemical measurements using [Ru(NH3 )6 ] 3+, [Fe(CN)6 ] 3−, and ferrocenylmethanol [Fe(η 5 -C5 H4 CH2 OH)(η 5 -C5 H5 )] redox probes indicate that the alkynyl C–Au contacted monolayer of1 presents a relatively low barrier for electron transfer. This contrasts with monolayer films on gold of other oligo(phenylene ethynylene) derivatives of comparable length and surface coverage, but with different contacting groups. Additionally, a low voltage transition ( V trans = 0.51 V) from direct tunneling (rectangular barrier) to field emission (triangular barrier) is observed. This low transition voltage points to a low tunneling barrier, which is consistent with the facile electron transport observed through the C–Au contacted self-assembled monolayer of1 .